Air lime and natural hydraulic lime mortars with ceramic residues for rehabilitation of old buildings - Matias, Gina (2017)
Repair of old facades renders requires particular attention because raw materials currently available hardly ever correspond to the requirements for this purpose. Usually, in those cases, air lime mortars are more suitable; however, they imply long curing periods. Alternative solutions such as natural hydraulic lime mortars might reveal appropriate. In the past, it was also common the use of ceramic fragments and dust in mortars for plastering and rendering, which improved their behaviour. Considering the high amounts of residues currently produced by ceramic industries, the development of mortars with this residue might be a technically viable solution, and also respond to economic and environmental issues. In the present paper it is described a part of a large experimental campaign involving the characterization of air lime and natural hydraulic lime mortars with ceramic residues from bricks, roof tiles and pottery. A comparison is made between the results obtained for the two groups of mortars, considering physical and mechanical properties. Volumetric proportions of 1:2 (air lime mortars) and 1:4 (natural hydraulic lime mortars) were used and ceramic residues replaced 20%, 30% and 40% of the aggregate (common sand). The obtained results show that the incorporation of ceramics might provide significant changes in mortars porous structures and, consequently, in their mechanical and physical behaviour. Globally, when considering the studied properties, the analysed mortars may be regarded as suitable for rehabilitation purposes.